Tumor suppressor PNRC1 blocks rRNA maturation by recruiting the decapping complex to the nucleolus. (29th October 2018) - Gaviraghi, Marco; Vivori, Claudia; Pareja Sanchez, Yerma; Invernizzi, Francesca; Cattaneo, Angela; Santoliquido, Benedetta Maria; Frenquelli, Michela; Segalla, Simona; Bachi, Angela; Doglioni, Claudio; Pelechano, Vicent; Cittaro, Davide; et al.
Abstract: Focal deletions occur frequently in the cancer genome. However, the putative tumor‐suppressive genes residing within these regions have been difficult to pinpoint. To robustly identify these genes, we implemented a computational approach based on non‐negative matrix factorization, NMF, and interrogated the TCGA dataset. This analysis revealed a metagene signature including a small subset of genes showing pervasive hemizygous deletions, reduced expression in cancer patient samples, and nucleolar function. Amid the genes belonging to this signature, we have identified PNRC1, a nuclear receptor coactivator. We found that PNRC1 interacts with the cytoplasmic DCP1α/DCP2 decapping machinery and hauls it inside the nucleolus. PNRC1‐dependent nucleolar translocation of the decapping complex is associated with a decrease in the 5′‐capped U3 and U8 snoRNA fractions, hampering ribosomal RNA maturation. As a result, PNRC1 ablates the enhanced proliferation triggered by established oncogenes such as RAS and MYC. These observations uncover a previously undescribed mechanism of tumor suppression, whereby the cytoplasmic decapping machinery is hauled within nucleoli, tightly regulating ribosomal RNA maturation. Synopsis: Computational analysis of frequent cancer genome deletions reveals that PNRC1‐dependent nucleolar recruitment of the cytoplasmic mRNA decapping complex blocks ribosomal maturation and ablates oncogene‐induced cell proliferation. Nuclear receptor co‐activator PNRC1 is frequently deleted in cancer cells. PNRC1 interacts with the DCP1α/DCP2 decapping complex and stimulates its translocation into the nucleolus. PNRC1 expression blocks ribosomal RNA processing in cancer cells. The nucleolar PNRC1‐DCP1α/DCP2 complex targets the U3 and U8 snoRNAs for decapping. PNRC1 expression ablates oncogene‐induced proliferation, suggesting a tumor suppressive role. Abstract : Computational analysis of frequent cancer genome deletions reveals that mRNA decapping activity blocks ribosomal maturation and ablates oncogene‐induced proliferation.